PERNIKAHAN BEDA AGAMA (Membaca kitab al-Mahshul karya Imam Fakhr al-Din al-Razi) - alawiyah, tuti (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Differences in a marriage are considered normal, but if the difference is religion, this will cause problems because in the Marriage Law in Indonesia, namely Law Number 1 of 1974, in Article 2 paragraph (1), namely: Marriage is legal, if according to the laws of each religion and belief. With the provisions of this article, it can be interpreted that marriage can be said to be valid if the couple who wants to marry is of the same religion or belief. Therefore, the provisions in this Article, it is not uncommon for someone who wants to step into marriage but has a potential companion who is religious. The couple will change religions or do legal smuggling, to carry out the marriage. This article will explore interfaith marriage and how Imam Ar-Razy views in his book al-Mahshul fi al-Usul.